Demographic change and the labour share of income - Torsten Schmidt; Simeon Vosen (Journal of Population Economics, 2013)
Despite similar levels of per capita income, education and technology, the development of labour income shares in OECD countries has displayed different patterns since 1960. The paper examines the role of demography in this regard. We first use a standard overlapping generations model to derive the mechanisms by which demographic change can affect the labour share. It turns out that demographic change can affect the labour share either by altering the domestic capital intensity, by causing factor-biased technological change or in a small open economy framework by creating a gap between domestic savings and investments. The latter affects the country's investments abroad and in return its net foreign asset income which directly leads to changes in the labour share. Empirical estimations based on these insights, provide evidence that an increases in the expected retirement durations and old-age dependency ratios as well as declines in labour force growth rates have indeed been major forces behind the decline in labour shares that took place in many countries. These effects tend to be larger in open economies and pension reforms towards a funded pension system seem to have accelerated the effects.
Keywords: E25; J10; D91; C23; 330; Labour Share; Demographic Change; Capital Mobility; Panel Cointegration